Stonewall : a building. an uprising. a revolution. - Sanders, Rob, 1958- (Random House, 2019)
Describes the Stonewall Riots in New York City in 1969, which sparked the gay liberation movement in the United States, and details the history of LGBTQ rights since the riots.